Corrosion-Based Failure of Oxide-Aperture VCSELs - Herrick, R; Dafinca, A; Farthouat, P; Grillo, A; McMahon, S; Weidberg, A (2013)
Oxide vertical cavity surface emitting lasers (VCSELs) have been known to have a premature failure mode when operated in the presence of atmospheric water vapor, due to corrosion failure. However, information on the precise chain of failure has not previously been available. In this paper, we start by showing the field failure results in a large particle-physics application with 6,000 deployed channels. Next, evidence is shown for the chain of failure between the previously observed oxide aperture tip cracking and delamination, and how that appears to cause dark-line defect networks in the GaAs active region beneath the aperture. In addition, we show how corrosion can be monitored through spectral width narrowing and discuss other symptoms of corrosion-based degradation that show up hundreds or thousands of hours before the rapid failure takes place. Finally, possible ways of preventing corrosion-based failure are discussed. © 2013 IEEE.